Development Of Alginate-Gelatin Hydrogel Beads: A Baiting Tool For Dengue Vectors As Mosquito Control Strategy - Ayub, Noor Muokhni (2023)
We found that the mosquitoes achieved total mortality after consumption, and the number of female attempts to blood-feed also reduced after 6 hour of exposure. We conclude that the AGHBs are applicable as a baiting tool to carry the liquid bait in achieving mosquito mortality and at the same time reduced in blood-feeding.